Five years of Institutional Experience in the Evaluation and Management of Papillary Thyroid Microcarcinoma: Insights from the NINMAS (Bangladesh Journal of Nuclear Medicine, 2026)
Papillary thyroid microcarcinoma (PTMC) is defined by the World Health Organization as a papillary thyroid carcinoma (PTC) with the greatest dimensions ≤1.0 cm. Its incidence is increasing along with the rise of PTC. The purpose of this study was to observe the five-year clinical outcome of PTMC patients who were referred to the Thyroid Division, National Institute of Nuclear Medicine & Allied Sciences (NINMAS) after total thyroidectomy and followed up without radioactive iodine ablation therapy (RAIT). The record files of registered PTMC patients between January 2017 and December 2020 were retrospectively analyzed, and the overall outcome was evaluated. A total of 95 patients (M: F = 3:16), with a mean age of 43 ± 14.14 years, were included in the study. Initial mean thyroglobulin (Tg) was 12.3±0.57 ng/dl, while mean Tg in the last follow-up was 1.72±0.23 ng/dl. Most of the patients (96.84%) had an uneventful follow-up period. But three (3.16%) patients had shown recurrence and underwent revision neck surgery followed by radioiodine ablation. In these patients with recurrence, initial average Tg was 35.02 ng/dl, and last follow-up Tg was 0.20 ng/dl after RAIT. Histopathology of recurrent tissue in the thyroid bed and lymph nodes confirmed PTC. The results of this study reaffirm that papillary microcarcinoma has an excellent prognosis if managed initially by total thyroidectomy. However, appropriate counselling and patient awareness are required considering the small recurrence rate evaluated by this study.Bangladesh J. Nuclear Med. 28(2): 289-292, July 2025